Global, regional, and national burden of sudden infant death syndrome and the impact of COVID-19: a trend and health inequality analysis based on the global burden of disease study 2021 - Zheng, Xinkuo; Liu, Meishen; Zhao, Xingwei; Xu, Xiuqi; Tao, Wei; Wu, Ling; Sun, Weijia; Dong, Yuhang; Xi, Yalin (Frontiers in Pediatrics, 2025)
BackgroundCurrent sudden infant death syndrome (SIDS) epidemiological patterns and COVID-19 impacts remain uncertain. We therefore conducted this global, regional, and national epidemiological study using data from the Global Burden of Disease Study (GBD) 2021.MethodsThis study analyzed GBD-based population data on SIDS disability-adjusted life years (DALYs). Age-standardized DALY rates (ASDR; per 100,000 population) with 95% uncertainty intervals (UIs) were calculated for 204 countries and territories, stratified by age, location, and socio-demographic index (SDI).ResultsIn 2021, the ASDR of SIDS accounted for 44.16 (95% UI: 25.70–59.26) per 100,000 population globally, which was a 58.97% decrease from 1990. The low and low-middle SDI quintiles exhibited a disproportionately higher disease burden of SIDS among the five SDI quintiles in 2021. Higher sociodemographic status showed an inverse association with SIDS burden, with high-SDI countries demonstrating a greater reduction compared to low-SDI counterparts from 1990 to 2021 based on age-period-cohort analysis. Although the global burden of SIDS had maintained a sustained downward trend prior to the pandemic, COVID-19 disruptions may have attenuated mitigation progress, with trend analysis suggesting a possible plateau in SIDS burden during this period rather than continued decline. Study findings indicate that although the global incidence of SIDS has shown a steady decline, persistent regional disparities underscore long-standing public health challenges.ConclusionThe burden of SIDS-related DALYs remains substantial, and its post-pandemic evolution trends necessitate dynamic tracking through robust epidemiological surveillance systems.